Mycolactone-dependent depletion of endothelial cell thrombomodulin is strongly associated with fibrin deposition in buruli ulcer lesions - Ogbechi, Joy; Vogel, Moritz (PLoS pathogens, 2015)
Author Summary Buruli ulcer (BU) is a neglected tropical disease that is most common in West Africa and parts of Australia, but has been reported from over 30 countries worldwide. The symptoms are painless ulcers of the skin caused by a bacterial infection. The bacteria, Mycobacterium ulcerans, produce a macrolide toxin called mycolactone. In this manuscript, we have studied the effects of mycolactone on endothelial cells, specialised cells that line blood vessels and form capillaries. One of the most important functions of these cells is to prevent blood from clotting inside the vessels. We show that mycolactone reduces the ability of cultured endothelial cells to anticoagulate blood, by blocking the expression of a protein called thrombomodulin. We went on to examine samples of BU patient skin and found that thrombomodulin is also reduced here, and that in contrast to normal skin large amounts of fibrin (one of the main constituents of blood clots) were present. This means that it may be useful to consider whether anticoagulants might improve the response to antibiotics and thereby improve treatment outcomes for BU patients.